Consonant Production of an American-English Native Speaker from 3 to 6 Years Old: A Case Study on a Child named Brielle - Aghnia Dianah Anwar; Tofan Dwi Hardjanto (Universitas Veteran Bangun Nusantara, 2022)
ABSTRACTChildren’s phonological development is somewhat foreseeable, yet there are certain sounds that appear at different ages across children. However, there are some general guidelines which can be used to analyze the phonological development of a child. This study aims to examine the phonological development process of an American English native speaker named Brielle in producing consonants from the age of three to six using the speech sound development milestones provided by Sander (1972). The data are taken from youtube videos of Brielle when appearing on an American talkshow called “The Ellen Show”. A descriptive qualitative method is used in this study to elaborate the phonological development of Brielle. The result shows that Brielle completed her phonological development at the age of six. It can also be concluded from the study that some consonants appear earlier or later thatn the phonological development milestones set by Sander (1972). During the process of acquiring consonants, she replaced the consonant which she could not produce with another sound with similar features, such as replacing the liquid sound /l/ with the glide sound /j/.